Спиральные вакуумные токи квантового скалярного поля в моделях с нетривиальной топологией пространства - Саарян, А. А.; Симонян, Д. А.; Микаелян, А. Г.; Ванцян, А. А.
The vacuum expectation value of the current density is investigated for a massive scalar field in a (D+1)-dimensional flat space-time with compact dimension. Along a compact dimension, the field operator obeys the helical quasiperiodicity condition with a constant phase. In the special case of a zero helicity parameter, the results previously studied in the literature are obtained. In contrast to that case, the vacuum current, in addition to the component along the compact dimension, has a non-zero component in the direction of the non-compact dimension along which the field operator is shifted. A simple relation between those components is obtained. They are odd periodic functions of magnetic flux threading the compact dimension, with the period equal to the flux quantum. For a given non-zero value of the helicity parameter, the component of the vacuum current along the compact dimension tends to zero in the limit when the length of that dimension tends to zero. In the problem considered earlier with the usual quasiperiodic condition, the vacuum current diverges in that limit. Исследовано вакуумное среднее плотности тока массивного скалярного поля в (D+1)-мерном плоском пространстве-времени с компактным измерением. Вдоль компактного измерения оператор поля удовлетворяет спиральному условию квазипериодичности с постоянной фазой. В частном случае нулевого параметра спиральности получаются результаты, ранее исследованные в литературе. В отличие от этого случая, вакуумный ток, наряду с компонентой вдоль компактного измерения, имеет ненулевую компоненту по направлению некомпактного измерения, вдоль которого смещается оператор поля. Получено простое соотношение между этими компонентами. Они являются нечетными периодическими функциями магнитного потока, пронизывающего компактное измерение с периодом, равным кванту магнитного потока. При заданном ненулевом значении параметра спиральности компонента вакуумного тока вдоль компактного измерения стремится к нулю в пределе, когда длина этого измерения стремится к нулю. В рассмотренной ранее проблеме с обычным квазипериодическим условием в этом пределе вакуумный ток расходится.
Keywords: Физика